Marketing Opportunities for Perennial Peanut Hay, 2002 - Robert L. Degner; Kimberly L. Morgan; Thomas J. Stevens, III; Clay Olson (EDIS)
The overall objective of this study was to determine the awareness and use of perennial peanut hay among horse owners in Florida. Specific objectives were to determine the types of hay preferred by horse owners, relative quantities purchased, seasonality of demand, and prevailing prices. Other important objectives were to identify barriers to increased consumption of perennial peanut hay and to determine the sources of information used by horse owners in deciding what types of hay to buy. This is EDIS document FE424, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, UF/IFAS, University of Florida, Gainesville, FL. Published September 2003.